Unionization in a dynamic oligopolistic model of international trade - Asilis, Carlos M. (Estudios Económicos de El Colegio de México, 1992)
The study of dynamic strategic behavior in international trade environments with imperfect factor markets (unions) yields significantly different policy implications compared to those that obtain under static settings. We find that contrary to static equilibria, the equilibrium of our model exhibits renegotiation-proofness; unilateral implementation of cost subsidies may yield negative domestic welfare effects; and trade policy tools are not useful in pursuing rent-shifting objectives.